Top management characteristics and firm's international diversification activities: evidence from a developing nation - Amin Noordin, Bany Ariffin; McGowan, Carl B.; Tunde, Matemilola Bolaji; Shahnaz, Abd Salam (Universiti Putra Malaysia Press, 2014)
Recent trend shows that foreign investment has increased rapidly, and raises a question as to whether managerial characteristics impact international diversification, as claimed by the Uppsala internationalisation process theory. This paper investigates the relationship between top management team's characteristics and firm's Outward Foreign Direct Investment, that is, international diversification. This study focuses on 83 of the top 100 largest Malaysian multinational firms. The entropy measure is used as the proxy for level of international diversification. Age, international experience, educational level and functional background are proxies reflecting the management's cognitive abilities and competencies. The findings showed that age and functional background have significant positive influence on the level of international diversification. In addition, the results also suggested there is a reasonable support for upper echelons theory and Uppsala internationalisation process theory.